The Influence of Financial Literacy, Hedonic Lifestyle, Locus Of Control and Personal Financial Attitudes on Gen Z Financial Behavior in Sidoarjo - Hariyanto, Vicky Dwi; Sriyono, Sriyono; Setiyono, Wisnu Panggah (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to determine how financial literacy affects financial behavior in generation Z, how Hedonic Lifestyle affects financial behavior in generation Z, how Locus Of Control affects financial behavior, how financial attitudes affect financial behavior in generation Z. This type of research uses causal conclusive research. The population used is the population of Sidoarjo city aged 17-26 years. The sampling technique used is purposive sampling. The location of the study is in the city of Sidoarjo. From the data obtained, it will then be processed using the SmartPLS program. The results of the study are financial literacy, hedonic lifestyle, locus of control and financial attitudes have a positive effect on financial behavior.